If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 10 = 2y + -7 Reorder the terms: 10 + 3y = 2y + -7 Reorder the terms: 10 + 3y = -7 + 2y Solving 10 + 3y = -7 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 10 + 3y + -2y = -7 + 2y + -2y Combine like terms: 3y + -2y = 1y 10 + 1y = -7 + 2y + -2y Combine like terms: 2y + -2y = 0 10 + 1y = -7 + 0 10 + 1y = -7 Add '-10' to each side of the equation. 10 + -10 + 1y = -7 + -10 Combine like terms: 10 + -10 = 0 0 + 1y = -7 + -10 1y = -7 + -10 Combine like terms: -7 + -10 = -17 1y = -17 Divide each side by '1'. y = -17 Simplifying y = -17
| 4x^2=9x-3 | | 2k^2-3k-2=0 | | 2.1x^2+4.2=0 | | 3x-y= | | log(x+2)+log(x-1)=log(88) | | 119-3x=15x+17 | | 3-5*(4-5x)=-67 | | 16=4(8-z)2 | | 119-3x=15x+1 | | 9x+27=41+2x | | 8x+22=52-2x | | -3-6x=4x+23 | | 3x-1=2x-5 | | 10x+7=5x-14 | | 10x-190=10x+190 | | 7+7x=49+x | | 0.5x+0.5=11.5 | | 0.6x+0.5=11.5 | | 5(x-2)+3x= | | 7-2(5-2x)= | | 3(x+2)+4(x-5)= | | a-5+2a-8a=5 | | 2(x+3)-4x=5x-(3x-12)+8 | | 3x+4y=125 | | -3(x-5)=4x+5 | | y+.1=-22.4 | | 5(2x-3)+4(x+1)= | | 2(5p-q)-(p-3q)= | | y+0.11=-22.4 | | X*(X-3)=42 | | 5x-25-8x=3-8x+2x | | -4g=-28 |